Risk factors for checkpoint inhibitor pneumonitis in lung cancer patients treated with immune checkpoint inhibitors: a systematic review and meta-analysis - Zhou, Xiaoqing; Xu, Yingnan; Ying, Yuanyuan; Chen, Ruilin; Wang, Zhen; Lv, Xin (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) significantly improve survival in lung cancer patients. However, checkpoint inhibitor pneumonitis (CIP) remains a critical safety concern. This meta-analysis systematically evaluates demographic, clinical, and laboratory risk factors associated with CIP development to guide risk-stratified management.MethodsWe systematically searched eight databases from inception to February 20, 2025. Study quality was assessed using the NOS. Adjusted risk factors from multivariate analyses were pooled in RevMan 5.4. Sensitivity analyses addressed heterogeneity, and funnel plots evaluated publication bias.Results28 NOS-certified high-quality studies were included. 20 risk factors comprised: advanced age, male sex, smoking status, preexisting interstitial lung abnormalities, pulmonary fibrosis, COPD, thoracic radiotherapy history, squamous cell carcinoma histology (versus adenocarcinoma), early-stage NSCLC (Stage III versus IV), multifocal metastases (≥2 sites), PD-1 inhibitors (versus PD-L1 agents), elevated PD-L1 expression (≥50%), pembrolizumab use (versus nivolumab), AEC, CRP, PLR, WBC, and hypoalbuminemia. Sensitivity analyses confirmed consistency between FEM and REM; funnel plots indicated no publication bias.ConclusionThis study identifies 20 independent CIP risk factors in ICI-treated lung cancer patients. Early screening and intervention for high-risk populations are critical to reducing CIP incidence and improving clinical outcomes. These findings provide actionable insights for optimizing ICI safety in real-world practice.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/myprospero, identifier CRD420250655469.